2004
DOI: 10.1021/jm030432v
|View full text |Cite
|
Sign up to set email alerts
|

5-Substituted Derivatives of 6-Halogeno-3-((2-(S)-azetidinyl)methoxy)pyridine and 6-Halogeno-3-((2-(S)-pyrrolidinyl)methoxy)pyridine with Low Picomolar Affinity for α4β2 Nicotinic Acetylcholine Receptor and Wide Range of Lipophilicity:  Potential Probes for Imaging with Positron Emission Tomography

Abstract: Potential positron emission tomography (PET) ligands with low picomolar affinity at the nicotinic acetylcholine receptor (nAChR) and with lipophilicity (log D) ranging from -1.6 to +1.5 have been synthesized. Most members of the series, which are derivatives of 5-substituted-6-halogeno-A-85380, exhibited a higher binding affinity at alpha4beta2-nAChRs than epibatidine. An analysis, by molecular modeling, revealed an important role of the orientation of the additional heterocyclic ring on the binding affinity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 48 publications
0
53
0
1
Order By: Relevance
“…The kinetic drawbacks of existing nAChR radioligands (2-18 F-FA and 6-18 F-FA) prompted the development of radioligands with faster brain kinetics by our group and others (8)(9)(10)(11)(12)14,15,29). Studies in our labs on the radioligand structureimaging properties relationship (17,(30)(31)(32) led us to synthesize 18 F-AZAN, an a4b2-nAChR antagonist with rapid brain kinetics and high binding potential values in mice and baboons (17,18). Further, a blockade PET study (18) with the selective partial a4b2-nAChR agonist cytisine strongly suggested that 18 F-AZAN binds predominantly at a4b2-nAChRs.…”
Section: Discussionmentioning
confidence: 99%
“…The kinetic drawbacks of existing nAChR radioligands (2-18 F-FA and 6-18 F-FA) prompted the development of radioligands with faster brain kinetics by our group and others (8)(9)(10)(11)(12)14,15,29). Studies in our labs on the radioligand structureimaging properties relationship (17,(30)(31)(32) led us to synthesize 18 F-AZAN, an a4b2-nAChR antagonist with rapid brain kinetics and high binding potential values in mice and baboons (17,18). Further, a blockade PET study (18) with the selective partial a4b2-nAChR agonist cytisine strongly suggested that 18 F-AZAN binds predominantly at a4b2-nAChRs.…”
Section: Discussionmentioning
confidence: 99%
“…Many naturally occurring as well as synthetic compounds containing the pyridine scaffold exhibit interesting pharmacological properties [6][7][8][9][10]. Furthermore, pyridine is one of the most popular N-heteroaromatics incorporated into the structure of many pharmaceuticals.…”
Section: Introductionmentioning
confidence: 99%
“…The most successful leaving groups used in fluorine-18 nucleophilic aromatic substitution are nitro-as in [ 18 F]altanserin (Monclus, et al, 1992;Tan, et al, 1997) and [ 18 F]setoperone (Maziere, et al, 1988), quaternary ammonium (Wilson, et al, 1991), and some halides (Guenther et al, 2006;Willis et al, 2005;de Vries et al, 2003;Zhang et al, 2004;Fei et al, 2004;Roger et al, 2003). Normally, labeling reactions require an electronwithdrawing group ortho or para to the leaving group for reaction to occur, both by reducing electron density at the target carbon and by resonance stabilization of the putative sigma complex in an addition-elimination mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Suitable activating groups include nitro, carbonyl, and cyano substituents. Only a few halogenated compounds in highly activated aromatic rings with electron-withdrawing substituents have been studied for [ 18 F]labeling (Karramkam et al, 2003;Zhang et al, 2004;Dolci et al, 1999;Dischino et al, 2003;Al-Labadi et al, 2006). The application of microwave fluorodehalogenation to less reactive homoaromatic compounds has not been studied in detail, although Hamill et .…”
Section: Introductionmentioning
confidence: 99%